2019
DOI: 10.1136/bmjopen-2019-031484
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare providers’ perception of the referral system in maternal care facilities in Aceh, Indonesia: a cross-sectional study

Abstract: ObjectivesOur study investigates the barriers perceived by staff in the referral systems in maternal healthcare facilities across Aceh province in Indonesia.DesignWith a cross-sectional approach, two sets of surveys were administered during September to October 2016 in 32 sampling units of our study. We also collected referral data in the form of the frequency of ingoing and outgoing referral cases per facility.SettingIn three districts, Aceh Besar, Banda Aceh and Bireuen, a total of 32 facilities including ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 24 publications
2
31
1
1
Order By: Relevance
“…Among studies included in the review, a majority was from India (n=30, 48 %) . There were 11 studies from Nepal (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52) , 10 from Bangladesh (53)(54)(55)(56)(57)(58)(59)(60)(61)(62) , six from Indonesia (63)(64)(65)(66)(67)(68) and two from Timor-Leste 69,70 . From Bhutan 71 , Thailand 72 , and Myanmar 73 one from each was identi ed.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among studies included in the review, a majority was from India (n=30, 48 %) . There were 11 studies from Nepal (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52) , 10 from Bangladesh (53)(54)(55)(56)(57)(58)(59)(60)(61)(62) , six from Indonesia (63)(64)(65)(66)(67)(68) and two from Timor-Leste 69,70 . From Bhutan 71 , Thailand 72 , and Myanmar 73 one from each was identi ed.…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted among Nepal women has identi ed family support, transport availability and nearby birthing center as facilitators for institutional deliveries 52 . In Indonesia, a research revealed that all private and public hospitals in a province provide full coverage of Comprehensive Emergency Obstetric and New-born Care 64 . Support from friends, family and co-workers and male participation in accessing antenatal clinics are identi ed as enablers for early ANC booking in Bhutan 71 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations